Multifactorial analysis of football penalty kicks in the Portuguese First League: A replication study. Issue 1 (February 2023) - Almeida, Carlos Humberto; Volossovitch, Anna
Although penalty-kick outcomes in football are thought to be affected by different factors, many of them have not been sufficiently analysed yet. This study sought to replicate and extend the findings of a previous multifactorial analysis of penalty kicks in Union of European Football Associations (UEFA) club competitions. For that purpose, we used a larger sample ( n  = 833), collected from eight consecutive seasons of the Portuguese First League (from 2013–2014 to 2020–2021) and adding the variables season, team quality and the penalty taker's playing status (starter or substitute) to the analysis. Chi-square tests of independence only showed significant associations of performance-related factors ( shot horizontal and vertical directions, and goalkeeper's action ) with penalty-kick outcome . Multinomial logistic regression model revealed significant increases in the odds of penalty kicks being saved when (1) shots were directed to the centre-left zones compared to the right zones (penalty taker's perspective), (2) shots were directed to the low zones of the goal and (3) goalkeepers dived to the correct side of the ball. In addition, the probability of missing the target or hitting the goalpost/crossbar significantly increased when shots aimed the high zones of the goal. Noteworthy, the risk of a penalty being saved when the shot was directed to the bottom zones of the goal outweighed the "miss factor" of shooting high. These findings enable coaches to develop optimal strategies for taking and saving penalty kicks, thus increasing the likelihood of both players to succeed in competitive matches, regardless of individual attributes and/or casual competitive circumstances.